The effect of financial ratios on the financial performance in pharmaceutical sector companies - Niva; Diska Arliena Hafni (Proceeding International Conference on Accounting and Finance, 2023)
The purpose of this study was to determine the effect of current ratio, cash ratio, debt to asset ratio, debt to equity ratio, receivables turnover ratio, total asset turnover, gross profit margin, and return on assets on the financial performance of pharmaceutical companies listed on the BEI for 2015-2021. This research applied quantitative research. The population of this study was a pharmaceutical company listed on the Indonesia Stock Exchange and sampling using purposive sampling. The data collection technique used secondary data. Data analysis was carried out by classical assumption test and hypothesis testing using multiple linear regression analysis. The results showed that the debt to asset ratio and return on assets had a positive effect on financial performance, while the current ratio, cash ratio, debt to equity ratio, accounts receivable turnover ratio, total asset turnover, and gross profit margin had no effect on financial performance.